Strategic planning and its relationship to administrative excellence for the sports and school activity departments for the central and southern regions (Damu Journal of Sport Sciences, 2024)
The importance of the study was evident in the extent of strategic planning and its relationship to the administrative excellence of the sports and scouting activity departments to achieve success and the desired goals. The problem of the research was that the researchers noticed that there was a lack of interest in the strategic planning of the sports and scouting activity departments. Therefore, the research in this study decided to find out the strategic planning and its relationship to the administrative excellence of the sports and scouting activity departments. Sports and scouting activity. The objectives of the research were to identify the reality of strategic planning and administrative excellence for the sports and scouting activity departments in the general directorates of education for the central and southern regions and the relationship between them. The researchers used the descriptive approach using the survey method and correlational relationships to suit the nature of the problem and the objectives of the research. The research community was determined from (technical supervisors) There are (185) technical supervisors in the sports and scouting activity departments for the central and southern regions, in (9) education directorates for the year (2023-2024), and the total study sample was selected from them by a comprehensive enumeration method of (100%) because they are an available sample. The researchers concluded that workers in the departments of sports and scouting activities in the governorates of central and southern Iraq are well aware of the nature of strategic planning and administrative excellence in their departments in a good and precise manner through positive relations between workers and their colleagues, built on frankness, accuracy and clarity. This is what was confirmed by the answers of the technical supervisors to the standards, and that the reality of planning Strategic and administrative excellence among the sample studied is high in various fields, and there is a significant correlation between the two study measures for workers in the sports and scouting activity departments for the central and southern region of Iraq.